Cardiac magnetic resonance-guided cardiac ablation: a case series of an early experience. (26th April 2023) - De Zan, Giulia; Calò, Leonardo; Borrelli, Alessio; Guglielmo, Marco; De Ruvo, Ermenegildo; Rier, Sophie; van Driel, Vincent; Ramanna, Hemanth; Patti, Giuseppe; Rebecchi, Marco; Fusco, Armando; Stefanini, Matteo; et al.
Abstract: Radiofrequency (RF) catheter ablation has become a widely used therapeutic approach. However, long-term results in terms of arrhythmia recurrence are still suboptimal. Cardiac magnetic resonance (CMR) could offer a valuable tool to overcome this limitation, with the possibility of targeting the arrhythmic substrate and evaluating the location, depth, and possible gaps of RF lesions. Moreover, real-time CMR-guided procedures offer a radiation-free approach with an evaluation of anatomical structures, substrates, RF lesions, and possible complications during a single procedure. The first steps in the field have been made with cavotricuspid isthmus ablation, showing similar procedural duration and success rate to standard fluoroscopy-guided procedures, while allowing visualization of anatomic structures and RF lesions. These promising results open the path for further studies in the context of more complex arrhythmias, like atrial fibrillation and ventricular tachycardias. Of note, setting up an interventional CMR (iCMR) centre requires safety and technical standards, mostly related to the need for CMR-compatible equipment and medical staff's educational training. For the cardiac imagers, it is fundamental to provide correct CMR sequences for catheter tracking and guide RF delivery. At the same time, the electrophysiologist needs a rapid interpretation of CMR images during the procedures. The aim of this paper is first to review the logistic and technical aspects of setting up an iCMR suite. Then, we will describe the experience in iCMR-guided flutter ablations of two European centres, Policlinico Casilino in Rome, Italy, and Haga Teaching Hospital in The Hague, the Netherlands.